PENGARUH LAMA FERMENTASI SECARA ANAEROB CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO TERHADAP KARAKTERISTIK ALKOHOL - Aditya Wirajaya, I Kadek; Ganda Putra, Gusti Putu; Semadi Antara, Nyoman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2016)
The objective of the research was to determine the effect of fermentation time and the optimal fermentation time producing the highest alcohol content of the product. This study used a randomized block design with fermentation time as a treatment which was consists of 11 levels namely 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 days. The results showed that the naturally anaerobic fermentation time did not affect the alcohol content, pH, total dissolved solids of the alkohol product. The treatment of natural fermentation for 5 days was an appropriate treatment to produce alcohol with the characteristics of the alcohol content of 2.05%(w/w), acidity (pH) 3.41, total dissolved solids 5,30 brix, 0.216% total acid. Keywords: alcohol, liquid pulp, fermentation time
Keywords: 91